Metal Hydride Composite Structures for Improved Heat Transfer and Stability for Hydrogen Storage and Compression Applications - Liang Liu; Alexander Ilyushechkin; Daniel Liang; Ashleigh Cousins; Wendy Tian; Cherry Chen; Jon Yin; Liezl Schoeman (Inorganics, 2023)
Metal alloys and intermetallic compounds offer an attractive method for safely storing hydrogen (H2). The metal alloys absorb H2 into their structure, often swelling and fracturing as a result of phase transformation during hydride formation/decomposition cycles. The absorption of H2 is an exothermic process, requiring the effective and efficient removal of heat. This can be challenging as heat transfer to/from powdered beds is notoriously difficult, and often limited by poor thermal conductivity. Hence, the observed reaction kinetics for absorption and desorption of H2 is dominated by heat flow. The most common method for improving the thermal conductivity of the alloy powders is to prepare them into composite structures with other high thermal conductivity materials, such as carbons and expanded natural graphite. Such composite structures, some also combined with polymers/resins, can also mitigate safety issues related to swelling and improve cyclic durability. This paper reviews the methods that have been used to prepare such composite structures and evaluates the observed impact on thermal conductivity.